FAMILY RESISTANCE IN ESTABLISHMENT THE END OF CHILDREN ACCORDING TO PSYCHOLOGICAL - Asnawi, Asnawi (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2019)
The discussion is about parents' strategies in empowering children's potential to display behavior with moral content to their relationship with God, their fellow human beings and the natural environment in accordance with their nature. But in practice in life, it is not realized perfectly. As a result, it is common to find more children who are less obedient to worship, less polite and dissent to parents. Occurring quarrels with peers are also indifferent, less concerned about the environment as part of the negative nature of the child. The next negative impression is like wild, commotion, noise, anti-advice, not caring for the natural environment and difficult to accept the truth. To anticipate this, parents need to improve empowerment by maintaining knowledge that has been provided and applied a psychology approach, so that a touch of soul feeling unites in behavior to get closer to God, has a noble character, especially parents, and morality towards the environment. Does not give an opportunity to commit a disgraceful act.Technical data collection using qualitative descriptive methods, namely the technique of collecting data through notes, writings and documents from various literary sources that have relevance and support the objects discussed. While processing data, the descriptive analysis method is used, which is presenting or explaining the data that has been collected. The object of this research is the attitude and behavior of children towards obedience in worship, fellow humans and their concern for the environment. Family resilience in shaping children's morals, parents can do by teaching, leading, guiding, guiding, supervising and getting used to. Children to be commendable, so that children can apply in life. Furthermore, parents maintain the nature of the ability and willingness of the child, motivate him to increase moral awareness of God by realizing as a god of worship, and himself as a servant, polite and polite fellow humans as loyal friends, especially their parents as caregivers and educators, caring, friendly to nature and its preservation as its domicile.